POLITICAL MARKETING MIX DAN PENGARUHNYA TERHADAP KEPUTUSAN MAHASISWA UNIVERSITAS LAMPUNG - Ridho Bramulya Ikhsan; Muchsin Saggaff Shihab (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2010)
The purpose of this study is to scrutinize the effect of the political marketing mix on the voters’ decision. The concept of political marketing mix i.e. product, promotion, price and place were employed in this study. Both primary and secondary data were obtained. Secondary data were obtained from various sources such as journal, and books. Primary data were obtained by using questionnaire. Target respondents were students of Lampung University (UNILA) who voted for the 2010 Mayor election at Bandarlampung. Using stratified random sampling with proportional distribution and accidental sampling techniques, a total of 100 responses were obtained. Data were examined using both descriptive and statistical analysis such as, linear regression analysis, validity and reliability tests. Findings showed that, partially and simultaneously, political marketing mix which includes product, promotion, price and place had a significant impact on voters’ decision. Of all factors, place was found to be dominant. Keywords: Political Marketing, Marketing Mix, voters’ decision.